Water security and livelihoods in the arid zones of South Africa: a human geography approach to rural education and curriculum development - Tolulope Ayodeji Olatoye; Raymond Nkwenti Fru (Frontiers in Education)
Water insecurity poses a critical threat to livelihoods in South Africa’s arid zones, where rural communities are increasingly vulnerable to hydrological stress, ecological degradation, and socio-economic marginalization. Despite the urgency of the issue, scholarly engagement that bridges water security with rural development education through a human geography perspective remains underexplored. Also, inadequate integration of local ecological knowledge and community-driven water management strategies into formal education systems undermines both resilience and innovation in rural development initiatives. This study conducts a systematic literature review of policy papers and peer-reviewed articles drawn from Scopus and Web of Science databases to investigate the nexus between water security and livelihoods in South Africa’s arid regions, with a focus on its pedagogical relevance to rural education development. Guided by the Sustainable Livelihoods Framework (SLF), the findings reveal that water scarcity is a deeply social and spatial condition shaped by historical land dispossession, poor infrastructure, climate variability, and fragmented governance, hence, the urgent need to recalibrate rural education curricula to incorporate interdisciplinary, context-specific knowledge on water governance, environmental justice, and sustainable livelihoods. This study recommends a transformative educational model that embeds water security into human geography, environmental science, and rural development programs, which prioritizes experiential learning, participatory research, and transdisciplinary partnerships to foster water-literate graduates and empowered rural citizens. Hence, this study reimagines education as a tool for adaptation, equity, and charts a new course for integrating water justice into the heart of rural transformation in South Africa’s arid landscapes.